Facile synthesis of rubrolide E - Kar, Anirban; N. P. Argade (Synthesis-Stuttgart, 2005)
A simple and efficient synthesis of rubrolide E (1e) has been demonstrated via Meerwein coupling reaction of para-anisyl-diazonium chloride with N-phenylmaleimide (2), regioselective reduction of para-anisylmaleic anhydride (4), Knoevenagel condensation of butyrolactone 5 with para-anisaldehyde and demethylation pathway.
Keywords: Knoevenagel condensation; Meerwein coupling; N-phenylmaleimide; regioselective reduction; rubrolide E; Total synthesis

Concise synthesis of (-)-deoxoprosopinine - Pandey, Satyendra Kumar; Kumar, Pradeep (Synlett, 2007)
A simple and highly efficient approach to (-)-deoxoprosopinine from racemic epoxide as a starting material is described employing a Jacobsen's hydrolytic kinetic resolution (HKR) and Sharpless asymmetric dihydroxylation (AD) as key steps.
Keywords: hydroboration-oxidation; Jacobsen's HKR; Piperidine alkaloids; sharpless AD; Total synthesis

Expeditious assembly of 3,4-benzannulated 8-oxabicyclo[3.2.1]octane systems by [2+2+2] alkyne cyclotrimerisation: Total synthesis of (-)-bruguierol A - Ramana, Chepuri V.; Salian, Sumanth R.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2007)
Facile construction of benzene-fused 8-oxabicyclo[3.2.1]octane systems by employing a cross alkyne cyclotrimerisation reaction was explored. With this procedure, (-)-bruguierol A was synthesised, and its absolute configuration was established.
Keywords: cyclotrimerisation; epoxidation; Total synthesis; Wilkinson's catalyst

Short and efficient synthesis of rubrolide E - Chavan, Subhash P.; Pathak, Ashok B.; Pandey, Ankur; Kalkote, Uttam R. (Synthetic Communications, 2007)
Short and efficient synthesis of rubrolide E from commercially available 4-methoxyacetophenone, employing ring-closing metathesis, Knoevenagel condensation, and Reformatsky reactions, are the key steps are described.
Keywords: antibiotics; antitumor; Epoxide; Natural products; Total synthesis

Total synthesis of pulchellalactam via an RCM strategy - Chavan, Subhash P.; Pathak, Ashok B.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synthetic Communications, 2007)
Total synthesis of (Z) pulchellalactam, a CD protein tyrosine phosphatase inhibitor, from commercially available methallyl chloride employing ring-closure metathesis (RCM) as a key step is described.
Keywords: alkaloid; Natural products; pulchellalactam; RCM; Total synthesis

First asymmetric total synthesis of penarolide sulfate A(1) - Mohapatra, Debendra K.; Bhattasali, Debabrata; Gujar, Mukund K.; Khan, Mohammad Islam; Shashidhara, K. S. (European Journal of Organic Chemistry, 2008)
Penarolide sulfate A(1), with three contiguous stereogenic centers on a macrocyclic skeleton, affords promise as an alpha-glucosidase inhibitor. Herein, we describe the first asymmetric total synthesis of this natural product. A stereoselective strategy for rapid assembly of the complete framework of the 30-membered macrocyclic core is delineated herein. Sequential amidation and intramolecular Sonogashira cross-coupling reactions were pivotal to the success of our efforts. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: Asymmetric synthesis; C-C coupling; Dihydroxylation; epoxidation; Macrocycles; Regioselectivity; Total synthesis

Enantio- and diastereocontrolled total synthesis of (+)-strictifolione - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Naidu, S. Vasudeva; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2010)
A concise and practical enantioselective synthesis of (+)-strictifolione has been achieved in high diastereomeric excess using Jacobsen's hydrolytic kinetic resolution, proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde and cross olefin/ring-closing metathesis as the key steps.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; lactones; Natural products; organocatalysis; Ring-closing metathesis; Total synthesis

Enantioselective total syntheses of (-)-isonitramine, (-)-sibirine, and (+)-nitramine by ring-closing metathesis - Pandey, Ganesh; Kumara, Prasanna C.; Burugu, Shiva Kumar; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
Concise enantioselective total syntheses of naturally occurring 2-azaspiro[5,5]undecan-7-ol (Nitraria) alkaloids viz. ()-isonitramine, ()-sibirine, and (+)-nitramine are accomplished in 42, 38, and 25?% overall yield, respectively, in six steps starting from enantiomerically pure (S)-methyl 3-allyl-2-oxo-1,2,3,6-tetrahydropyridine-3-carboxylate (>99?%?ee). The key feature of the syntheses involves diastereoselective HosomiSakurai allylation followed by ring-closing metathesis.
Keywords: Alk-aloids; Allylation; Amino alcohols; Metathesis; Total synthesis

Intramolecular chemoselective acylation of a suitably substituted isoindole: synthesis of (+/-)-chilenine and (+/-)-deoxychilenine - Wakchaure, Prasad B.; N. P. Argade (Synthesis-Stuttgart, 2011)
Starting from 3,4-dimethoxyhomophthalic anhydride and 6-bromohomopiperonylamine, concise and efficient syntheses of Chilean berberis products chilenine and deoxychilenine have been demonstrated via partially divergent routes by taking advantage of facile air-oxidation of homophthalimide along with intramolecular chemoselective acylation as the key steps.
Keywords: chemoselective acylation; chilenine; deoxychilenine; homophthalic anhydride; isoindole; Total synthesis

InCl3-mediated addition of indole to isatogens: an expeditious synthesis of 13-deoxy-isatisine A - Kumar, Chepuri V. Suneel; Puranik, Vedavati G.; Ramana, Chepuri V. (Chemistry-A European Journal, 2012)
A strategy directed towards the total synthesis of isatisine A that involves several late-stage metal-catalyzed transformations that address the key carboncarbon and carbonheteroatom bond formations has been developed. As a part of this strategy, methods for the addition of indoles to isatogens that lead selectively to either 2,2-disubstituted N-hydroxyindolin-3-one or 2,2-disubstituted indolin-3-one compounds have been developed by employing InCl3 as a catalyst or as the reagent. The present methods provide the first examples of the additions of indoles to the isatogen nucleus. To demonstrate its viability, the synthesis of 13-deoxy-isatisine A has been completed in ten steps from a known and easily available lactone.
Keywords: indium; indoles; isatogens; Natural products; Total synthesis

Palladium-catalyzed routes to geranylated or farnesylated phenolic stilbenes: synthesis of pawhuskin C and schweinfurthin J - Singh, Mandeep; N. P. Argade (Synthesis-Stuttgart, 2012)
Starting from double MOM-protected phloroglucinol, the facile total syntheses of bioactive natural products pawhuskin C and schweinfurthin J were accomplished in good overall yields. The Heck, Stille, or Suzuki coupling reactions of two different electron-rich phenolic segments bearing geranylated or farnesylated units were involved in the decisive step. The Sonogashira coupling reaction followed by palladium-catalyzed chemo-and stereoselective cis-reduction of an alkyne unit and subsequent isomerization to give the desired natural products is also described.
Keywords: geranylated or farnesylated stilbenes; Natural products; palladium-catalyzed coupling reactions; phloroglucinol; Total synthesis

Synthesis of isomeric corniculatolides - Raut, Gajanan N.; Chakraborty, Kasturi; Verma, Priyanka; Gokhale, Rajesh S.; Reddy, D. Srinivasa (Tetrahedron Letters, 2012)
Synthesis of three natural macrolides 11-O-methylcorniculatolide A, 11-O-methylisocorniculatolide A and isocorniculatolide A is reported using a simple, straight forward and high-yielding route. The present synthesis confirms the assigned molecular structures and provides an access to sufficient quantities of the natural products for the biological evaluation. In addition, we have determined the anti-TB potential of the three natural compounds using Alamar-Blue assay (H(37)Rv) and found no significant inhibitory activity at 100 mu g/ml. Excellent yields, short sequence and useful SAR information are the highlights of the present work. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Diaryl ether; Isocorniculatolide; Macrocyclization; Mitsunobu reaction; Total synthesis

Synthesis of a sex pheromone of the longtailed mealybug, pseudococcus longispinus - Kurhade, Suresh E.; Siddaiah, V.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2013)
The synthesis of a recently identified and highly active sex pheromone of the longtailed mealybug, Pseudococcus longispinus is reported. A concise synthetic route, use of the under explored Meyer-Schuster rearrangement, Claisen rearrangement, and ring-closing metathesis are the highlights of this work.
Keywords: Acylation; Metathesis; pheromones; rearrangement; Total synthesis

Total synthesis of umuravumbolide and hyptolide through silicon-tethered ring-closing metathesis - Chowdhury, Partha Sarathi; Kumar, Pradeep (European Journal of Organic Chemistry, 2013)
The total synthesis of umuravumbolide and hyptolide has been achieved in a efficient manner by using temporary silicon-tethered ring-closing metathesis and cross-coupling reactions as key steps. The stereogenic centres were generated by means of proline-catalysed -aminoxylation of aldehydes and Brown's asymmetric allylation method.
Keywords: lactones; Metathesis; Silanes; synthetic methods; Total synthesis; Wittig reactions

Concise account of the chemistry of valuable alkyl(methyl)maleic anhydrides - Deore, Prashant S.; Haval, Kishan P.; Gadre, Smita R.; N. P. Argade (Synthesis-Stuttgart, 2014)
A large number of significant bioactive natural and synthetic alkyl(methyl)maleic anhydrides are known in the contemporary literature. A broad range of suitably functionalized substrates have been tailored to accomplish concise and efficient syntheses of an array of alkyl(methyl)maleic anhydrides employing a variety of elegant synthetic strategies. This review presents a brief literature account of the isolation and activity of these important target compounds with a special emphasis on their synthesis.
Keywords: alkyl(methyl)maleic anhydrides; bioactivity; dimethylmaleic anhydride; isolation; nucleophilic reactions; Total synthesis

Protecting-group-free diastereoselective total synthesis of (+/-)-6-epi-cleistenolide and chemoenzymatic synthesis of (-)-6-epi-cleistenolide - Mahajan, Pankaj S.; Gonnade, Rajesh G.; Mhaske, Santosh B. (European Journal of Organic Chemistry, 2014)
A short, efficient, practical, and protecting-group-free diastereoselective total synthesis of (+/-)-6-epi-cleistenolide (1) has been achieved in five steps in 60% overall yield. The use of a chemoenzymatic approach also gave (-)-6-epi-cleistenolide (1) (>99.9% ee). The Achmatowicz reaction, chemoselective oxidation of a hemiacetal, diastereoselective 1,3-anti reduction of alpha-hydroxy ketone, and enzymatic resolution of a 1,3-diol are the key features of this linear total synthesis. The synthetic strategy demonstrated in this paper could be extended for an asymmetric total synthesis of (-)-cleistenolide (1) and related biologically active natural products.
Keywords: Asymmetric synthesis; diastereoselectivity; Enzyme catalysis; Lipases; Oxygen heterocycles; Total synthesis

Total synthesis of mangiferaelactone - Vadhadiya, Paresh M.; Ramana, C. V. (Tetrahedron Letters, 2014)
Herein we document the first total synthesis of mangiferaelactone and thus establish its absolute configuration. The central nonenolide ring was constructed using ring closing metathesis and Yamaguchi esterification. The key alcohol fragment was synthesized by the Bernet-Vasella fragmentation of C-ribofuranoside. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Bernet-Vasella fragmentation; Nonenolide; Ring closing metathesis; Total synthesis; Yamaguchi protocol

Total synthesis of the putative structure of xylarinol B - More, Atul A.; Ramana, Chepuri V. (Chemistry-An Asian Journal, 2014)
The total synthesis of the putative structure of xylarinolB is described and the need to revise its structure is demonstrated. The central benzoxepine skeleton was constructed by employing a cobalt-mediated bimolecular [2+2+2] Reppe-Vollhardt alkyne cycloaddition reaction.
Keywords: Chiral pool; cobalt; Natural products; structure elucidation; Total synthesis

Efficient organocatalytic route for asymmetric total synthesis of stagonolide F - Shelke, Anil M.; Suryavanshi, Gurunath (Tetrahedron Letters, 2015)
A stereoselective total synthesis of Stagonolide F (98% ee) is described employing asymmetric alpha-aminooxylation, Jorgensen's asymmetric epoxidation, Brown asymmetric allylation, Steglich esterification and ring closing metathesis as key steps. The use of organocatalytic alpha-aminooxylation and Jorgensen's asymmetric epoxidation of aldehydes for the introduction of chirality makes this approach more attractive. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: alpha-Aminooxylation; Jorgensens's asymmetric epoxidation; Macrolide; Ring-closing metathesis; Total synthesis

First enantioselective synthesis of surinamensinol B and a non-natural polysphorin analogue by a two-stereocentered hydrolytic kinetic resolution - Lalwani, Komal G.; Sudalai, Arumugam (European Journal of Organic Chemistry, 2015)
An efficient and economical approach to the synthesis of antitumor and anti-inflammatory surinamensinol B (1) and antimalarial polysphorin analogue 2 has been achieved with high enantiomeric purity (96% ee) by starting from commercially available 3,4,5-trimethoxybenzaldehyde. The key steps of the strategy include a Co-catalyzed two-stereocentered hydrolytic kinetic resolution (HKR) of racemic 2[( methoxymethoxy)(3,4,5-trimethoxyphenyl)methyl] oxirane (13) as the chiral inducing step followed by a Mitsunobu reaction. Chiral epoxide 14 and chiral diol 15 were utilized in the syntheses of both compounds.
Keywords: Biological activity; Enantioselectivity; Kinetic resolution; Natural products; Total synthesis

Formal total synthesis of (-)-kumausallene - Das, Shyamsundar; Ramana, Chepuri V. (Tetrahedron, 2015)
Deacetylkumausyne-a penultimate intermediate in Tang's total synthesis of (-)-kumausallene has been synthesized employing a chiral pool approach and thus culminating in a formal total synthesis of kumausallene. The opening of an epoxide with alkyne (use of Birch reduction for the selective construction of E-pent-3-enyl group) and C-allylation have been used to introduce the pendant alkenyl side chains. Initial attempts to execute an alternative to Tang's route comprising a prior installation of the bromoallene unit via bromoetherification and subsequent S(N)2 displacement are unsuccessful. To overcome this, an alternative approach was developed to arrive at Deacetylkumausyne (another natural product that has been synthesized and characterized by Tang's group). Thus, this overall exercise has culminated in a formal total synthesis of (-)-kumausallene. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bis-THF natural products; Chiral pool; Deacetylkumausyne; Total synthesis; Wittig reaction

Total and semi-syntheses of antimicrobial thuggacin derivatives - Franke, Jana; Bock, Martin; Dehn, Richard; Fohrer, Joerg; Mhaske, Santosh B.; Migliorini, Antonella; Kanakis, Argyrios A.; Jansen, Rolf; Herrmann, Jennifer; Mueller, Rolf; Kirschning, Andreas (Chemistry-A European Journal, 2015)
The total and semi-synthesis of 13 new macrolactones derived from thuggacin, which is a secondary metabolite from the myxobacterium Sorangium cellulosum, are reported. The thuggacins have attracted much attention due to their strong antibacterial activity, particularly towards Mycobacterium tuberculosis. This study focuses on 1) thuggacin derivatives that cannot equilibrate by transacylation between the three natural thuggacins A-C, 2) the roles of the thiazole ring, and 3) the hexyl side chain at C2. Semi-synthetic O-methylation at C17 suppressed the transacylations without a substantial loss of antibacterial activity. Exchanging the C17-C25 side chain for simplified hydrophobic chains led to complete loss of antibacterial activity. Exchange of the thiazole by an oxazole ring or removal of the hexyl side chain at C2 had no substantial effect on the biological properties.
Keywords: antibiotics; lactones; Natural products; synthesis design; Total synthesis

Total syntheses and biological evaluation of (+/-)-botryosphaeridione, (+/-)-pleodendione, 4-epi-periconianone B, and analogues - Handore, Kishor L.; Jadhav, Prakash D.; Hazra, Bibhabasu; Basu, Anirban; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
The total syntheses of (+/-)-botryosphaeridione, (+/-)-pleodendione, (+/-)-hoaensieremodione, 4-epi-periconianone B, and their analogues have been accomplished for the first time. All the synthesized target compounds were screened in neural anti-inflammatory assays using LPS induced microglia cells (N9). Among them, compounds 1 and 21 were identified as potential lead compounds for further profiling.
Keywords: antineuroinflammatoty agents; bohyosphaeridione; Natural product; pleodendione; Total synthesis

Total synthesis of (+)-petromyroxol - Mullapudi, Venkanna Babu; Ramana, Chepuri V. (Tetrahedron Letters, 2015)
The total synthesis of (+)-petromyroxol establishing its absolute configuration has been accomplished. The strategy developed employs easily accessible carbohydrate building blocks and comprises flexible and scalable chemistry that allowed the synthesis of (+)-petromyroxol along with its three diastereomers varying the stereochemistry mainly at C5 and/or C6. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Glucose diacetonide; Petromyroxol; Pheromone; Sea Lamprey; Total synthesis

Total synthesis of (-)-nardoaristolone B - Ople, Rohini S.; Handore, Kishor L.; Kamat, Nidhi S.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2016)
A stereoselective total synthesis of (-)-Nardoaristolone B, a nor-aristolane sesquiterpenoid natural product with an unusual 3/5/6 tricyclic ring system is described. The highlights of the present work includes use of (+)-(R)-Pulegone as a chiral-pool starting material, ring-closing metathesis, allylic oxidation and stereoselective cyclopropanation. In addition, a new analogue of Nardoaristolone B (minor product from the final step) was isolated in pure form and fully characterized with the help of single-crystal X-ray analysis.
Keywords: Chiral pool; cyclopropanation; Nardoaristolone B; Natural products; Total synthesis

Achmatowicz reaction: A versatile tool in bioactive natural products synthesis - Mahajan, Pankaj S.; Humne, Vivek T.; Mhaske, Santosh B. (Current Organic Chemistry, 2017)
Achmatowicz reaction has emerged as an efficient tool in organic synthesis since its discovery in 1971 by Achmatowicz Jr. The original protocol went through several advantageous variations. Biocatalytic and metal catalyzed versions of this reaction are some of the significant achievements, which further enhanced its effectiveness. The pyranone product of the Achmatowicz reaction is a versatile building block for the synthesis of bioactive scaffolds, drugs and natural products. The present review covers the application of the Achmatowicz reaction in the synthesis of natural products and bioactive molecules reported from 1971 to date. It has been divided into seven sections on the basis of the core structures of the natural products synthesized utilizing the Achmatowicz reaction. We believe that this comprehensive review will attract many more organic chemists to explore its utility in organic synthesis, especially in the synthesis of bioactive natural products as well as drugs in their efficient and atom economical synthesis.
Keywords: Achmatowicz reaction; carbohydrates; Furanols; Natural products; pyranones; Total synthesis

First total synthesis of (+/-)-rhodoconferimide - Pandhade, Kailas R.; N. P. Argade (Synthesis-Stuttgart, 2018)
Starting from vanillin and dimethyl maleate, a concise and efficient racemic total synthesis of the potent antioxidant marine natural product (+/-)-rhodoconferimide has been carried out via the Wittig reaction, catalytic hydrogenation, selective brominations, and imide formation. An appropriate regioselective double bromination of the aromatic ring was a key step in the synthesis.
Keywords: (+/-)-rhodoconferimide; Antioxidants; Bromination; Natural products; Total synthesis; Vanillin

First total synthesis of the proposed structure of pandangolide 1 - Show, Krishanu; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2018)
The first total synthesis of the proposed structure of pandangolide 1 is reported. The synthesis was carried out using both an organocatalytic approach and a chiral-pool approach. The required stereochemistry at C-3 and C-5 was installed by using an organocatalytic aldol reaction and a stereoselective ketone reduction. The construction of the 12-membered core was achieved by 2-methyl-6-nitrobenzoic anhydride-mediated Shiina lactonization. The structure of target molecule was confirmed unambiguously by single-crystal X-ray analysis, but the optical rotation and NMR spectroscopic data of the synthetic pandangolide 1 were found to be inconsistent with the natural product.
Keywords: lactones; Macrocycles; Natural products; structure elucidation; synthesis design; Total synthesis

Scalable synthesis of cladosporin - Das, Pronay; Mankad, Yash; Reddy, D. Srinivasa (Tetrahedron Letters, 2019)
Cladosporin, a secondary metabolite isolated from fungal sources like Cladosporium cladosporioides and Aspergillus flavus was found to exhibit selective nano-molar activity against malarial parasite Plasmodium falciparum by inhibiting parasitic protein biosynthesis. In addition, this natural product has a broad range of bioactivities including, antiparasitic, antifungal, antibacterial as well as plant growth inhibition. However, it has limited availability from the natural sources for further development. Herein, we report a modified and improved synthetic route which led us to produce this potent natural product in a gram scale. Conversion of the undesired diastereomer to desired one via Mitsunobu inversion of secondary alcohol and carbon monoxide insertion reaction towards the construction of isocoumarin unit are the key features of the present synthesis. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Anti-malarials; Cladosporin; Mitsunobu; Total synthesis

Attempted synthesis of central furopyran core of diocollettines A via a gold-catalyzed cascade 1,6-diyne cycloisomerization process - Mullapudi, Venkannababu; Ramana, V, Chepuri (Tetrahedron Letters, 2020)
Herein, we describe an Au-catalyzed cascade diyne cycloisomerization process that was projected to construct the central furopyran bicyclic core of Diocollettines A. Our intended strategy for the annulation of the third thf ring is based on epoxidation and subsequent intramolecular acetalization. However, the initial alkynol cyclization occurred in an undesired 5-exo-dig mode, ultimately leading to an undesired furopyran. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: 1; 6-Hexadiyne; Alkynol cycloisomerization; Diocollettines A; Gold-catalysis; Total synthesis

Total synthesis and absolute configuration determination of Ktedonoketone, a benzenoid metabolite from Thermophilic bacterium - Dandawate, Monica; Choudhury, Rahul; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Tetrahedron Letters, 2020)
The successful total synthesis of both enantiomers of ktedonoketone allowed us to decipher an unambiguous assignment of absolute configuration of the natural product. The concise synthesis highlights Wacker oxidation and aldol condensation as key steps. In addition to this, the current synthetic route is suitable to access a library of compounds on the similar skeleton as one can use readily available amino acids and Grignard reagents as variants. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Absolute configuration; Ktedonoketone; Total synthesis; Wacker oxidation

Total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate and its antimicrobial potentials - Said, Madhukar S.; Udavant, Rohini; Sahu, Amit Kumar; Khan, Abujunaid; Nayak, Rashmi; Dastager, Syed G.; Kumar, Pradeep; Gajbhiye, Jayant (Natural Product Research, 2020)
The first total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate (butenolide cinnamate) was achieved using commercially available starting material. The synthesized compound was found to have promising antibacterial activity against Gram-negative strainsEscherichia coli(ATCC 8739),Salmonella typhimurium(ATCC 23564) andPseudomonas aeruginosa(ATCC 19154) with a minimum inhibitory concentration of 2.0 mu g/mL, 1.0 mu g/mL and 2.0 mu g/mL, respectively. Notably, the compound was more potent against Gram-negative test strains than the Gram-positive test strains.
Keywords: antibacterial activity; butenolide cinnamate; Total synthesis

Total synthesis of twelve membered resorcyclic acid lactones, (R)-penicimenolide A, (R)-resorcyclide and (R)-dihydroresorcyclide - Das, Pronay; Reddy, D. Srinivasa (Tetrahedron, 2021)
Resorcyclic Acid Lactones or RALs are a class of fungal secondary polyketides isolated from a variety of fungal strains like Lasiodiplodia theobromae, Penicillium sp., Syncephalastrum racemosum etc. This class of macrocyclic lactones are found to exhibit a broad spectrum of biological activities and are of significant synthetic importance. Herein, we report the first total synthesis of (R)-penicimenolide A, twelve membered RAL (RAL12) isolated from Penicillium sp. (NO. SYP-F-7919). Besides, we also report the total synthesis of two other members, namely, (R)-trans-resorcyclide and (R)-dihydroresorcyclide. In the course of synthesis, we have utilized ring closing metathesis (RCM) as the key step in constructing the core macrolactone scaffold. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Macrocycle; Natural product; organic synthesis; Total synthesis

Concise approach for the synthesis of the tetracyclic framework of Lycibarbarines A and B - Shet, Manoj N.; Nechooli, Hemanth K.; Ramana, Chepuri V. (Tetrahedron Letters, 2023)
A simple approach for the construction of the tetracyclic spiroketal skeleton of Lycibarbarine A and B has been described. Employing a solvent free condition for epoxide opening with tetrahydroquinoline as a key reaction to couple both the fragments, an oxidation followed by TBAF-mediated silyl deprotection spiroketalization establishes the complete tetracyclic core present in these natural products. (c) 2023 Elsevier Ltd. All rights reserved.
Keywords: Chiral pool approach; D -Glyceraldehyde; Tetracyclic spiroketal; Total synthesis

Identification of new modulator of DNA repairing pathways based on natural product (±)-peharmaline A - Kulkarni, Akshay S.; Dash, Anshurekha; Shingare, Rahul D.; Chand, Jagdish; Manhas, Diksha; Singh, Aman; Nandi, Utpal; Goswami, Anindya; Reddy, D. Srinivasa (Bioorganic & Medicinal Chemistry, 2023)
The complex heterogenic environment of tumour mass often leads to drug resistance and facilitate chemo insensitivity triggering more malignant phenotypes among cancer patients. Major DNA-damaging cancer drugs have been consistently proven unsuccessful in terms of elevating chemo-resistance. (& PLUSMN;)-peharmaline A, a hybrid natural product isolated from seeds of Peganum harmala L. possesses significant cytotoxic activities. Herein, we have described the design, and synthesis of a novel library of close and simplified analogues around the anticancer natural product (& PLUSMN;)-peharmaline A and investigated their cytotoxic activities, which led to the identification of three structurally simplified lead compounds exhibiting better potency than parent natural product. Among them, demethoxy analogue of peharmaline A was further investigated for its anticancer potential eliciting demethoxy analogue as potent DNA-damage inducing agent attenuating the expression of the proteins responsible for the DNA damage repair. Therefore, this demethoxy analogue warrants detailed investigations for the confirmations of the molecular mechanism-based studies responsible for its anticancer activity.
Keywords: DNA damage; EMT; Pictet; Spengler reaction; Structure-activity relationship; Total synthesis

Total and diverted total synthesis of pyrrolo-quinazolinone alkaloids and their analogues - Rasapalli, Sivappa; Huang, Yanchang; Sammeta, Vamshikrishna Reddy; Alshehry, Reem; Anver, Fazmina; Shivasankar, Krishnamoorthy; Chavan, Subash P. (ChemistrySelect, 2023)
A short and expeditious total and diverted total synthesis of luotonin, vasicinone, and their analogues has been achieved from the key tricyclic quinazolinone intermediate which was accessed from simple substituted anthranilamide obtained from the coupling of & beta;-alanate with isatoic anhydride followed by Dieckmann condensation chemistry of the resulting diester. The tricyclic ketone exhibited interesting chemical properties, e. g. keto-enol tautomerism. Friedlander condensation and Fischer-Indolization were employed for further annulations to access polycyclic alkaloids and their analogues. A short and expeditious total and diverted total synthesis of Luotonin, Vasicinone, and their analogues has been achieved from the key tricyclic quinazolinone ketone that was accessed via Dieckmann condensation chemistry of the diester which was in turn obtained from the isatoic anhydride followed by cyclodehydration. The keto-enol tautomerism of the tricyclic ketone has been studied through 1H NMR. Friedlander condensation and Fischer-Indolization were employed for further annulations on to the tricyclic ketone to yield luotonins and nor-rutaecarpines in good yields.image
Keywords: Luotonin; Quinazolinone; Rutaecarpine; Total synthesis; Vasicinone

The first enantioselective total synthesis of the eremophilane-type sesquiterpenoid (-)-peniroqueforin C - Ingale, Sudhir R.; Vinodkumar, Ramavath; Kontham, Ravindar (Tetrahedron Letters, 2025)
Herein, we report the first stereoselective total synthesis of the eremophilane-type sesquiterpenoid (-)-peniroqueforin C using a chiral-pool strategy. This synthetic route features the use of readily available (S)-(+)-carvone as a chiral building block, Robinson annulation to construct the decalin system, substrate-controlled stereoselective methylation, single-step annulative construction of a tricyclic gamma-ylidene-butenolide with concomitant alkene transposition, and direct lactone-to-lactam conversion as key transformations.
Keywords: annulation reactions; Eremophilanes; Peniroqueforin C; Sesquiterpenoids; Total synthesis

Stereoselective strategies for the synthesis of functionalized cis-hydrindanes in natural product synthesis - Survase, Vijayanand U.; Handore, Kishor L. (European Journal of Organic Chemistry, 2025)
The cis-hydrindane motif is a bicyclic structure commonly found in many natural products that exhibit significant biological activity. This structural feature is present in a variety of bioactive compounds, particularly terpenoids, steroids, and alkaloids, which are known for their therapeutic potential, including anti-inflammatory, antimicrobial, antiviral, and anticancer properties. Due to its prevalence and biological relevance, the cis-hydrindane framework has attracted considerable attention from synthetic chemists, who have devoted substantial effort toward developing efficient and diverse methods for constructing this important motif. Many of the synthesized cis-hydrindane compounds have been used as key intermediates or building blocks in the total synthesis of complex natural products. This review provides an overview of strategic approaches for synthesizing functionalized cis-hydrindanes and its derivatives from 2000 to the present day, focusing on their application in natural product synthesis. By examining the diverse methods and their impact on natural product synthesis, this review will underscore the enduring importance of the cis-hydrindane framework in both synthetic organic chemistry and medicinal chemistry.
Keywords: annulation; Cis-hydrindane; Diel-Alder reaction; Natural products; Total synthesis

Total synthesis of isatisindigoticanine H - Wabale, Krishna R.; Ramana, Chepuri Venkata (Synthesis-Stuttgart, 2025)
The first total synthesis of the naturally occurring isatisindigoticanine H has been completed by employing D-mannitol as the chiral pool precursor to install the requisite stereochemistry of the natural product. Construction of the thiazole unit by dehydrative cyclization of a alpha-halo ketone with thiourea followed by Sandmeyer's reaction and subsequent nucleophilic addition of lithiated bromothiazole to the Weinreb amide are the key reactions employed in this regard.
Keywords: Chiral pool approach; Indothiazinone; Isatisindigoticanine H; Sandmeyer reaction; Total synthesis